2011
DOI: 10.1007/s10804-011-9134-y
|View full text |Cite
|
Sign up to set email alerts
|

Affording Emerging Adulthood: Parental Financial Assistance of their College-Aged Children

Abstract: The purpose of this study was to examine parents' attitudes about and patterns of providing financial assistance to their children during college, and how varying levels of parental financial support were related to children's beliefs (e.g., perceptions of adulthood), behaviors (e.g., work hours, drinking, and drug use), and identity development. The sample consisted of 402 undergraduate students (62% women) recruited from four college sites across the United States (M age = 19.89), and one of their parents (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…Quantitative research has revealed a relationship between parental resources and students' reported financial independence. Xiao et al (2014) found that students whose parents had higher incomes and assets were less likely to report financial independence than those with lower levels; in a similar vein, -Walker et al (2012) found that parents with the lowest income levels, who provided the least financial support to their student children, were more likely to consider their child to be an adult. Thus, a lack of financial support encouraged, if not forced, young people into taking on adult characteristics such as financial independence.…”
Section: Parental Contributions and Financial (In)dependencementioning
confidence: 87%
“…Quantitative research has revealed a relationship between parental resources and students' reported financial independence. Xiao et al (2014) found that students whose parents had higher incomes and assets were less likely to report financial independence than those with lower levels; in a similar vein, -Walker et al (2012) found that parents with the lowest income levels, who provided the least financial support to their student children, were more likely to consider their child to be an adult. Thus, a lack of financial support encouraged, if not forced, young people into taking on adult characteristics such as financial independence.…”
Section: Parental Contributions and Financial (In)dependencementioning
confidence: 87%
“…During this developmental period, parents greatly vary in the extent to which they accept the growing independence of their children (Kloep & Hendry, 2010). Although parents expect older adolescents who enroll in college to be more emotionally autonomous than college students do themselves (Baete Kenyon & Silverberg Koerner, 2009), parents in the United States are willing to provide financial support to college‐enrolled children to varying degrees (Padilla‐Walker, Nelson, & Carroll, 2012). More so than earlier in adolescence, parents of older adolescents expect that their children will function independently by engaging in activities such as maintaining full‐time employment, supporting themselves at least partially, enrolling in higher education, or living away from home.…”
Section: Parental Autonomy Support In Late Adolescencementioning
confidence: 99%
“…For example, over 50% of undergraduate students have parents who assist them with tuition and other costs associated with college life (e.g., cafeteria food and recreational activities). The average amount of money parents pay ranges from $5,000 to $30,000 annually (Padilla-Walker, Nelson, & Carroll, 2012). In addition to financial assistance, parents might help emerging adults navigate difficult decision-making situations by giving advice or by providing networking opportunities.…”
Section: Parentally Bereaved College Studentsmentioning
confidence: 99%